1995
DOI: 10.1021/bi00029a039
|View full text |Cite
|
Sign up to set email alerts
|

Stable photobleaching of P840 in Chlorobium reaction center preparations: Presence of the 42-kDa bacteriochlorophyll a protein and a 17-kDa polypeptide

Abstract: Simple procedures for the anaerobic preparation of photoactive and stable P840 reaction centers from Chlorobium tepidum and Chlorobium limicola in good yield are presented and quantitated. The subunit composition was tested by cosedimentation in sucrose density gradients. For C. limicola, it minimally comprises four subunits: the P840 reaction center protein PscA, the BChla antenna protein FMO, the FeS protein PscB with centers A and B, and a positively charged 17-kDa protein denoted PscD. The preparation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 45 publications
4
48
0
Order By: Relevance
“…Chlorosome-free membranes were prepared, and the molar ratio of BChl a to P840 was estimated on the basis of the oxidized minus reduced difference spectra, as summarized in Table II. The ratio of BChl a/P840 in the membranes of wild-type cells was estimated to be 49, in agreement with previous reports (12,36,37), whereas the ratio obtained in the ⌬pscD membranes was 43. These results suggested that the FMO proteins were partially detached from the mutant membranes during the preparation and that the low efficiency in the energy transfer between FMO protein and RC would reflect some distorted organization of FMO protein.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Chlorosome-free membranes were prepared, and the molar ratio of BChl a to P840 was estimated on the basis of the oxidized minus reduced difference spectra, as summarized in Table II. The ratio of BChl a/P840 in the membranes of wild-type cells was estimated to be 49, in agreement with previous reports (12,36,37), whereas the ratio obtained in the ⌬pscD membranes was 43. These results suggested that the FMO proteins were partially detached from the mutant membranes during the preparation and that the low efficiency in the energy transfer between FMO protein and RC would reflect some distorted organization of FMO protein.…”
Section: Discussionsupporting
confidence: 92%
“…PscD of C. tepidum, 143 residues; PsaD of Synechocystis sp. PCC 6803, 141 residues) and share similar distributions of charged basic residues, as previously mentioned by Hager-Braun et al (12). This is in clear contrast to the case that the amino acid sequences of F A /F B and core proteins show more divergent aspects between Chlorobium RC and photosystem I.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our attempts were to improve the resolution of 2-DE by separation of the associated chlorosomes on the membranes. In contrast to other nonionic detergents, Triton X-100 was highly effective for the solubilization of the membranes of C. tepidum and the separation of the chlorosomes as aggregates [23]. Optimal results were obtained using the protocol as described in [15].…”
Section: Triton X-100 Treatmentmentioning
confidence: 99%